A review on designing electronic books for children with autism - Beili, Wang; Ramli, Saiful Hasley; Na, Dai (Human Resource Management Academic Research Society, 2023)
Individuals with autism spectrum disorders often benefit from technology-based interventions. Technologies being marketed to the autism community and relevant published research are proliferating. As a neural developmental disorder, autism spectrum disorder brings great challenges to families of children with autism and society as a whole. Preschool intervention, assisted by parents, is capable of enabling autistic children to acquire life skills quickly and efficiently. A picture book, a commonly known tool of art therapy, was proven beneficial for preschool education. Meanwhile, modern technology has provided more interactive and educational opportunities for traditional picture books. Therefore, the behavioral characteristics of autistic children are analyzed, and the related design theories and principles of e-books are obtained through the method of literature review so as to provide theoretical support for the research on product design for edutainment for autistic children.